Analisis Termogravimetri Terhadap Pembakaran Pelet Biomassa Campuran - Sudarno, Sudarno; Budi Harsanto, Aris (JURNAL AGRI-TEK, 2014)
This study aims to investigate the magnitude of the activation energy of combustion of pellets with TGA method with a temperature rate of 20  C / min in air atmosphere. Pellets are made from a mixture of two types namely biomass sawdust and rice husk. Each of the previous biomass is pulverized to mesh 20 + / 40 - and 40 + / 60-.Pelet made with some variation of the percentage composition of the mixture by weight of rice husk into sawdust 0%, 25%, 50%, 75% and 100% on each powder size. Results and analysis of data obtained on the composition of 25% sawdust and rice husk 75% yield the lowest value of the activation energy of combustion is equal to Ea = 12183.34 J / Mol of powder size 20 + / 40 -. While the process of burning powder pellets of size 40 + / 60 - much longer than the size of the powder 20 + / 40 - .Keywords: TGA, Burning, Pellet, Activation Energy